PENENTUAN WAKTU OPERASIONAL UPS PADA SISTEM CATU DAYA OTOMATIS TRANSISI PLN-GENSET - Pambudi, Prastyono Eko; Duniawan, Agus; Fahmi, Samsuhadi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2019)
PLN main source of power supply from PLN is very influential on electricity supply for the community. Electrical energy from PLN sometimes often occur blackouts. The need for reliable power supply is indispensable to residential consumers, especially in home industries. From these problems, this research is conducted to realize the control system used to transition the power supply with the main power supply from PLN and backup power supply from Uninterruptible power supply (UPS) and Genset. This study produces an automatic power supply transition which has two backup power supplies in the form of UPS and Genset. From the analysis of residential houses that have PLN 450 VA subscription, the system will work with a 12 Volt UPS battery at a current capacity of 28,125 A, and a capacity of Genset 800 VA. The automatic power supply transition system will instruct the UPS power supply to be connected when the PLN main supply is disconnected, after a UPS battery low will command the Genset for the starter, and when the generator is in stable condition the power supply will switch to the power supply Genset. At the time of PLN power supply source again available load will be transferred system to PLN source.